أهمية دراسة اللغة العربية في فهم معاني القرآن (دراسة عن الفعل العربي) - Aidillah Suja (PERADA, 2019)
الدراسة عن اللغة العربية هي دراسة جذّابة على دراستها، هذه اللغة ليست لغة اتصالية فحسب، بل إنها لغة الهية لأن مصدران في الإسلام وهما القرآن والحديث تكتبا باللغة العربية. ولمعرفة القرآن والحديث معرفة تامّة وجب علينا فهم قواعد اللغة العربية منها "الفعل" و "الاسم" و "الحرف". بفهم تلك القواعد تسهّلنا على معرفة معاني القرآن والحديث معرفة تامّة. في هذا البحث قد بحث الباحث أحد من دراسة اللغة العربية وهي عن "الفعل" في القرآن الكريم. موضوع البحث هو "الفعل"، أمّا نوع البحث هو البحث المكتبي، طريقة جمع البيانات هي المراقبة وبقراءة الكتب المتعلقة بالبحث، وطريقة تحليل البيانات هي طريقة تحليل المضمون وهي بتحليل الكتب المتعلقة والآيات القرآنية المتعلقة بالبحث. النتيجة من هذا البحث هي أنّ دراسة اللغة العربية "الفعل" لها دور عظيم في فهم القرآن الكريم وهذه الدراسة تسهّل المسلمين على معرفة معاني القرآن معرفة تامة. فمن الدراسة التي قام بها الباحث من قبل كثير من الطلاب الجامعي أخطأ في فهم آية القرآن خصوصا ما يتعلق بأسلوب الذي فيه "الفعل"، ولكن بعد أن يتعلموا اللغة العربية عن "الفعل" خصوصا فيقدر على فهم بعض آية القرآن فهما جيدا. فبمؤسس على ما سبق ذكره أخذ الباحث الاستنباط أن الدراسة عن اللغة العربية واجبة على كل مسلم ومسلمة، خصوصا للطلاب الجامعي باعتبار أنّهم الأجيل المستقبلة. Learning about study of arabic language is very interesting to learnd, it is not only about complex comunication language but also devine revelation language for Muslim where two of refrences of islamic syari’ah is Al-qur’an and Hadist writed with arabic language. In addition to understand the Al-qur’an and Hadist must cognize several structure, grammatical of arabic language such as “verb” in arabic langguage, “isim” and “Harfun”. To understanding gramatical of arabic language or basic of arabic langguage inderectly a reader easier to understand Ilahi Verces. In this study, “verb” as one of Arabic language learning in Al-Qur’an was investigated by the researcher. The objects of study were “verb”. The research design used was literature study. The data were collected by observation and collecting the references related to the study and then were analyzed by using content analysis of the Ayahs of Al-Qur’an related to the study. The result showed that the Arabic language learning about “verb” has a great role which helps Muslim to comprehend the meaning of Ayahs of Al-Qur’an verb well. Then, it was also found that there were many students that were still misunderstanding in comprehending Al-Qur’an, specifically the parts containing “verb”. After they learn it, they were able to comprehend those Ayahs well. Therefore, it can be concluded that learning Arabic language is a compulsory for Muslim, especially for student because they are future generation.